ҚОРАҚАЛПОҒИСТОНДА МАДАНИЯТ СОҲАЛАРИ РИВОЖЛАНИШИНИНГ АСОСИЙ ТЕНДЕНЦИЯЛАРИ ВА ҲОЛАТИ (2017-2023 йиллар) - Хужаниязов, У.Е. (SCIENCE and SOCIETY, 2025)
This research article describes the achievements in the field of culture and art of the Republic of Karakalpakstan in 2017-2023.
Keywords: independence; culture; art; theatre; festival; reform; performance; international; music; pop